Implementasi Investasi Hijau dan Strategi daya Saing Hijau Terhadap Green Banking di Kota Surakarta - Awatara, I Gusti Putu Diva; Hamdani, Anwar (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
The implementation of green banking principle is reflected in a series of initiatives for the community program, community development and business programs, and encourages investment in more responsible businesses as a form of Bank's high concern for the environment. This study aims to analyze Green Investment, and Green Competitive Strategies that have an impact on the implementation of Green Banking in Surakarta City. This research was a survey conducted on bank customer in Surakarta City. The sample in this study was 75 respondents. Data collection methods use in this study were questionnaire and observation. The analysis technique used includes the test of the research instrument, namely the validity and reliability test; classic assumption test include: heteroscedasticity, autocorrelation, normality and multicollinearity test. Hypothesis test is done by using multiple linear regression analysis, t test, F test and analysis of the coefficient of determination (R2). The results of this study indicate that green investment and green competitive strategies have an impact on the implementation of green banking in Surakarta City. The variable that has the greatest impact is Green Competitive Strategies.